2020
DOI: 10.3390/v12020213
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Adenovirus 5 E1A Exon 1 Deletion Mutants in the Viral Replicative Cycle

Abstract: Human adenovirus infection is driven by Early region 1A (E1A) proteins, which are the first proteins expressed following the delivery of the viral genome to the cellular nucleus. E1A is responsible for reprogramming the infected cell to support virus replication alongside the activation of expression of all viral transcriptional units during the course of the infection. Although E1A has been extensively studied, most of these studies have focused on understanding the conserved region functions outside of a ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
(77 reference statements)
2
7
0
Order By: Relevance
“…ARGLU1 was knocked-down via siRNA transfection followed by infection and determination of viral titer 24 and 48 h after infection with HAdV-C5 dl 309 (Figure 2E ). Depletion of ARGLU1 had an overall enhancing effect on virus growth, similar to what we previously observed with the mutant dl 1102 ( 43 ), with viral titers increasing approximately 2-fold with ARGLU1 knockdown versus siControl-treated cells. The enhanced virus growth correlated with enhanced viral gene expression when ARGLU1 was knocked down (Figure 2F ), similarly to what we previously have observed in E1A mutants that no longer bind ARGLU1 ( 43 ).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…ARGLU1 was knocked-down via siRNA transfection followed by infection and determination of viral titer 24 and 48 h after infection with HAdV-C5 dl 309 (Figure 2E ). Depletion of ARGLU1 had an overall enhancing effect on virus growth, similar to what we previously observed with the mutant dl 1102 ( 43 ), with viral titers increasing approximately 2-fold with ARGLU1 knockdown versus siControl-treated cells. The enhanced virus growth correlated with enhanced viral gene expression when ARGLU1 was knocked down (Figure 2F ), similarly to what we previously have observed in E1A mutants that no longer bind ARGLU1 ( 43 ).…”
Section: Resultssupporting
confidence: 85%
“…We have previously characterized the effects of deletion of E1A in the two mutants that have impaired binding to ARGLU1 ( dl 1102 and dl 1103) in primary lung fibroblasts WI-38 ( 43 ). Interestingly, we observed that mutant dl 1102 initially grew better than the in vitro phenotypically wild-type (wt) virus strain dl 309, with this mutant growing particularly well 48 and 72 h after infection and expressing its genes to higher levels than wt HAdV-C5, while mutant dl 1103 grew much worse than wt despite expressing its genes at a similar level to the wt virus ( 43 ). To determine whether knockdown of ARGLU1 affects viral replicative cycle in a similar way to deletion of its interaction region in E1A, we performed siRNA-mediated ARGLU1 knockdown studies.…”
Section: Resultsmentioning
confidence: 99%
“…As previously described by Costa et al [ 47 ] and Graves et al [ 27 ], 293 cells were plated and then subsequently infected at a MOI 10 with either Ad.shHBO1 or Ad.shLuc in serum free media for 1 h. At the indicated time points, cells were imaged in the bright field at 20× magnification using the BioRad ZOE cell imager.…”
Section: Methodsmentioning
confidence: 99%
“…Real-time gene expression was performed as previously described ( 20 , 21 ). Briefly, 293 cells were infected in triplicate with each indicated viral construct at an MOI of 10 vp/cell for 24 h. Total RNA was extracted using TRI reagent (MilliporeSigma) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%